English Society and Its Depiction in Selected Works by Agatha Christie - Štěpánková, Aneta (Univerzita Pardubice, 2013)
The aim of this thesis is to compare selected novels by Agatha Christie and the comprehensive historical studies. The first part focuses on characterizing crime fiction genre and its development from its beginning, the Golden Age is described in detail. The second part of the work examines the system of English social classes and their stereotypical images in Agatha Christie's fiction of the 1930s which are considered the peak of Christie's writing. The last part deals with the portrayal of Christie's women and their attitudes towards recently acquired equality of rights. The thesis will conclude by providing information about whether Christie mirrored English society faithfully.
Anglická společnost a její zobrazení ve vybraných dílech Agathy Christie
Keywords: Christie, Agatha; English society; social class; crime fiction; twentieth century; Christie, Agatha; anglická společnost; společenská třída; detektivní žánr; dvacáté století